The Study of Career and Family Values Among College Going Females - Safeena Naaz (International Journal of Indian Psychȯlogy, 2025)
This study examines the impact of religion and socio-economic status on career and family values among college-going females in Ranchi. With increasing access to education and evolving societal norms, women’s career aspirations and family roles are undergoing significant changes. The study utilized a purposive sampling technique, selecting 80 participants from various colleges in Ranchi. Data were collected using the Career and Family Values Scale and analyzed through statistical methods. The findings indicate that neither religion nor socio-economic status significantly affects career or family values, as demonstrated by the non-significant t-values. This suggests that career aspirations are shaped more by personal ambition, educational opportunities, and societal transformations rather than by traditional religious or economic factors. The results align with previous studies (Eldor et al., 2019; Gopalan & Pattusamy, 2020) that emphasize personal determination and work-life balance over socio-economic influences. Furthermore, family values remain stable across religious and economic backgrounds, contradicting prior research (Kumar, 2021; Rao et al., 2024) that suggested stronger cultural and economic influences. The study highlights the need for career counseling that focuses on skill development, mentorship, and psychological support rather than religious or financial backgrounds. However, the study is limited by its small sample size and geographic scope. Future research should include larger, more diverse populations and qualitative methods to gain deeper insights into the evolving career and family values of women in contemporary society.